The influence of push-up training on shooting ability in the handball game of Makassar City athletes - Akbar Yusuf; Ikadarny Ikadarny; Suparman Suparman; Davi Sofyan; Andi Sahrul Jahrir (Universitas Majalengka, 2023)
Makassar handball athletes who took part in the Porprov Exhibition Championship held in Makassar always had difficulty getting the ball into the opponent's goal. In this case, their shooting ability was still very weak, so the ball that was shot could be easily driven away or held by the opposing goalkeeper. The purpose of this study was to determine the effect of push-up training on the shooting ability of the Makassar City athlete's handball branch. The population of this study used a total sampling technique with a total of 14 athletes. This type of research uses a one-group pretest-posttest design. at the beginning (pretest) and end (posttest) of the treatment. This type of research has applications. Based on inferential statistical analysis using the t-test and a t-count value of 17.793 > ttable 2.160 (sig. value 0.000 0.05), it means that there is a significant effect after being given push-up training. To prove the increase in shooting ability, an average value of 4.333 is evidenced, or, in other words, the results of the t test obtained show that the t-count is greater than the t-table at a significant level of 0.05. So it can be concluded that there is a significant influence between push-up exercises (X) and the shooting ability (Y) of Makassar City handball athletes.